On The Modelling Of Complex Sociopsychological Systems With Some Reasoning About Kate, Jules, And Jim (Differential Equations and Nonlinear Mechanics)
This paper deals with the modelling of complex sociopsychological games and reciprocal feelings involving interacting individuals. The modelling is based on suitable developments of the methods of mathematical kinetic theory of active particles with special attention to modelling multiple interactions. A first approach to complexity analysis is proposed referring to both computational and modelling aspects.